PENGARUH KONTEN GAME STREAMING PADA KANAL YOUTUBE TERHADAP DEKADENSI AKHLAK GENERASI MUDA - ., Fadhil Rizqi Romdhoni (Nathiqiyyah, 2023)
Moral decadence is a form of social change in which moral conditions continue to decline. Moral decadence in today's younger generation occurs when the current of modernization can present everything indefinitely that affects the moral decline of the Indonesian population, especially young people. The issue of moral crisis experienced among young people is very broad. This is caused by many factors, one of which is the misuse of Youtube social media. As we currently know, the rise of streaming game content videos that contain harsh words, jokes that contain vulgar things, offend sara issues, and so on. As these contents become increasing, the bad habits displayed in the content carry over in real life. For example, saying indecent things towards friends, not showing respect for old people, calling sordid and rude designations to friends, and others. Thus, it is necessary to pay special attention to this social phenomenon.